Existence of Islamic Boarding Schools: Efforts to Build a Modern Education Mindset - Ahmad Zubaidi; Muhammad 'Ainur Ridlo (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This research focuses on Pesantren education to maintain its existence, not just alternative education to become a reference education for the community. The study aims to build a modern educational mindset of students and provide understanding to the broader community. This research approach is qualitative research. The research used is descriptive qualitative research. The data analysis model in this study uses techniques, namely data reduction, data exposure, and drawing conclusions and verification. The results of this study show that Pondok Pesantren Nurul Jadid is carrying out a pattern of learning education so that cottages and students are no longer left behind by the times and can compete outside and have also combined the pesantren curriculum and the national curriculum. Combining classical learning traditions with modern styles is well embodied in the teaching system and lessons. Not only limited to religious studies but also science educational pattern of the Nurul Jadid Islamic boarding school in the existence of pesantren efforts to build a modern academic mindset, the learning process of the Nurul Jadid Islamic boarding school began to make adjustments to the curriculum, methods, learning systems, materials and so on.